Validity Of The Media Booklet On Eubacteria Material Based On Research : Testing The Antibacterial Activity Of Moringa Leaf Extract (Moringa oleifera L.) - Asnilawati, Asnilawati -; Pratiwi, Chyndea -; Maretha, Delima Engga; Anggun, Diah Putri (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
In the contemporary educational landscape, the lecture or question-and-answer method remains prevalent, leading to infrequent use of media in the learning process. Consequently, students' creativity and interest in the subject matter can diminish. To determine the validity of the booklet media as a supportive resource and reference for class X SMA/MA eubacteria material. This study employs development research based on the ADDIE development model introduced by Dick and Carey, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Testing revealed that the analysis of learning media needs for eubacteria material at Muara Rupit State High School indicated that students' reliance on textbooks and teacher-provided summaries was suboptimal for the teaching process. Therefore, it is necessary to develop booklet media to assist students in cultivating critical thinking and scientific attitudes. It is important to continue developing booklet media and to test its practicality to ensure it can be effectively integrated into school learning environments